Exploring Interactions between Real Activity and the Financial Stance - Tor Jacobson; Jesper Lindé; Kasper Roszbach (Sveriges Riksbank, 2005)
In this paper we empirically study interactions between real activity and the financial stance. Using aggregate data we examine a number of candidate measures of the financial stance of the economy. We find strong evidence for substantial spillover effects on aggregate activity from our preferred measure. Given this result, we use a large micro data-set for corporate firms to develop a macro-micro model of the interaction between the financial and real economy. This approach implies that the impulse responses of a given aggregate shock will depend on the portfolio structure of firms at any given point in time.
Keywords: C41; G21; G33; G38; 330; Default-risk models; Business Cycles; Financial Stability; Price stability; Financial and real economy interaction